Circularly polarized end-fire antenna of low profile - Seah, Isabella Kim Ching (Nanyang Technological University, 2020)
This project is on circularly polarized end-fire antenna of low profile. This project aims to explore the possibility of using a high frequency simulation software to design a circularly polarized helical planar antenna with a higher frequency bandwidth. The first part of this project focuses on the recreation of a past research on helical planar antenna to familiarise the tools the simulation software has to offer and to understand the results obtained from simulation. The second part of this project is to then design and explore possible ways to modify an antenna such that it is working within the frequency range specified.